Toward a meaningful technology for instrumental music education: Teachers’ voice - Michałko, Aleksandra; Campo, Adriaan; Nijs, Luc; Leman, Marc; Van Dyck, Edith (Frontiers in Education, 2022)
In musical instrument training, researchers have gradually started exploring the potential of interactive technologies supporting learning processes and teaching methods. Although numerous technological tools have been proposed to enhance instrument learning and teaching, these methods rarely find their way into daily practice and teaching routines. In this study, we report data from an online survey study administered to violin and drum kit teachers. Results reveal distinct learning profiles of novice violin and drum kit students and exhibit a variety of teaching approaches towards adults and children. Furthermore, they provide more insight into teachers’ opinions on the use of virtual reality (VR) and smart wearable technologies in early instrumental training, as well as their attitudes regarding technology design. Overall, our findings highlight the importance of involving teachers in the initial stages of technology design to facilitate technology acceptance and adoption, prevent potential mismatches between requirements regarding technological functionality and actual user needs, and promote musical growth and skill acquisition.